Go east, young man: imagining the American West as the Orient - Francaviglia, Richard V., author; Utah State University Press, publisher (Colorado State University. Libraries, 2011)
Transference of orientalist images and identities to the American landscape and its inhabitants, especially in the West-in other words, portrayal of the West as the 'Orient'--has been a common aspect of American cultural history. Place names, such as the Jordan River or Pyramid Lake, offer notable examples, but the imagery and its varied meanings are more widespread and significant. Understanding that range and significance, especially to the western part of the continent, means coming to terms with the complicated, nuanced ideas of the Orient and of the North American continent that European Americans brought to the West. Such complexity is what historical geographer Richard Francaviglia unravels in this book. Since the publication of Edward Said's book, Orientalism, the term has come to signify something one-dimensionally negative. In essence, the orientalist vision was an ethnocentric characterization of the peoples of Asia (and Africa and the 'Near East') as exotic, primitive 'others' subject to conquest by the nations of Europe. That now well-established point, which expresses a postcolonial perspective, is critical, but Francaviglia suggest that it overlooks much variation and complexity in the views of historical actors and writers, many of whom thought of western places in terms of an idealized and romanticized Orient. It likewise neglects positive images and interpretations to focus on those of a decadent and ostensibly inferior East. We cannot understand well or fully what the pervasive orientalism found in western cultural history meant, says Francaviglia, if we focus only on its role as an intellectual engine for European imperialism. It did play that role as well in the American West. One only need think about characterizations of American Indians as Bedouins of the Plains destined for displacement by a settled frontier. Other roles for orientalism, though, from romantic to commercial ones, were also widely in play. In Go East, Young Man, Francaviglia explores a broad range of orientalist images deployed in the context of European settlement of the American West, and he unfolds their multiple significances.--Provided by publisher.
Introduction: the malleable landscape -- The frontier West as the Orient (ca. 1810/1920) -- The American Zahara: into and beyond the Great Western Plains -- In praise of pyramids: orientalizing the western interior -- Chosen people, chosen land: Utah as the Holy Land -- Finding new Eden: the American Southwest -- The Far East in the Far West: Chinese and Japanese California -- Syria on the Pacific: California as the Near/Middle East -- To ancient East by ocean united: the Pacific Northwest as Asia -- The modern West as the Orient (ca. 1920-2010) -- Lands of enchantment: the modern West as the Near/Middle East -- Another place and another time: the modern West as the Far East/Asia -- Conclusion full circle: imagining the Orient as the American West.
Keywords: West (U.S.) -- Civilization; Orientalism -- West (U.S.) -- History; United States -- Civilization -- Asian influences; Asia -- Foreign public opinion, American; United States -- Territorial expansion; East and West